(untitled) (Third Sector Social Economic Review, 2021)
The new type of coronavirus (Covid-19), which started to affect the whole world as of 2019, has caused and continues to bring radical changes in the lives of individuals. While countries prefer social isolation and closure, individuals and families have been affected by this situation and changes have begun to occur in many feelings, thoughts, attitudes and behaviors. Individuals have begun to be unable to perform many actions that involve communication and socialization that they perform in their daily life practices with the Covid-19 epidemic. It is expected that individuals’ working from home first and then spending most of their free time at home will have an impact on family communication and interactions. In addition, it is expected that changes in the loneliness levels of individuals will occur due to social isolation, social distance and staying away from crowded environments, or because many leisure places are closed. In this study, it is aimed to determine the changes in family communication and interactions, as well as the changing attitudes towards education, health and economy, and the levels of loneliness that students studying at various departments at Atatürk University have begun to feel/perceive with the Covid-19 epidemic. The Family Communication and Interaction Scale, which was developed for this purpose, and the UCLA Loneliness Scale, which were finalized by Demir (1989), were used. Data were collected online from Atatürk University students on a voluntary basis through these forms. The data obtained were analyzed with the SPSS 20 package program and as a result of the analysis, the fact that family members continue their lives on a home basis causes them to spend more time in social media environments and the excess of this time causes discussions, increases the sensitivity to health in the family, increases the use of supplements, and economically family It was found out that some of the participants had difficulty and started to worry, that some of the participants did not become lonely due to personal characteristics such as being extroverted, but that the other part’s perceived/feeled loneliness levels increased.